Peranan Advokat Dalam Pemberian Bantuan Hukum kepada Orang yang Tidak Mampu Berdasarkan UU No 16 Tahun 2011 tentang Bantuan Hukum - Dhea Kinanty; Pramestia Andini Putri; Fauziah Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Free legal assistance is one of an Advocate's most important responsibilities. Every Advocate is required by Clause 56 of the Criminal Law Procedures section to provide low-income clients with free legal representation. The fundamental obligation to provide free legal assistance is Equality Before the Law. "Advocates are obliged to provide free legal assistance to those who are poor and seek justice," states Article 1 Clause 22 of Law Number 18 of 2003 concerning Advocates. Keywords: free legal aid, advocates, equality before the law.